Aspek Hukum Terhadap Perlindungan Konsumen Atas Bocornya Data Pribadi Pada Online Marketplace Serta Penyelesaian Sengketanya - Mulia, Cherrya Prianti; Faridah, Hana (Peneliti.net, 2025)
The presence of online marketplaces has made shopping easier for consumers, but has also raised risks to the security of personal data. Leaks of consumer personal data in online marketplaces have become an issue that is increasingly increasing with the development of digital technology. In this context, the online marketplace is not only a place for buying and selling transactions, but also a place for storing sensitive consumer information. This research aims to analyze the things that cause data leaks in online marketplaces, to find out the protection of consumers against leaks of personal data and to find out how to resolve disputes over leaks of consumers' personal data. This research method uses a normative juridical method, which is legal research that examines written law from various aspects. The research results show that leaks of personal data in online marketplaces are divided into two factors, namely internal factors and external factors. Legal protection efforts for leaks of consumer personal data are divided into preventive legal protection efforts and repressive legal protection efforts. Then, resolving disputes that arise as a result of leaking personal data can be pursued through litigation and non-litigation